BAHASA KIASAN DALAM PUISI-PUISI KARYA ROBERT BURNS - PANGERANG, DEWI UTAMI PUTRI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT The title of this research is â€œFigurative Languange in Robert Burns Poemsâ€ It is an attempt to analyze and explain the figurative languange and categorize it in accordance with theÂ  types and meaning of figurative language itself. The objectives of this research are to identify, classify, and analyze descriptivelyÂ  the type of the figurative language in Robert Burns Poems used Laurance Perrineâ€™s Theory (1983). The result shows that this research can be summarized as follows: first, in the poems of Robert Burns, there are seven types of figurative language, including: personification, methaphors, simile, irony, symbols, synecdoche, and hyperbole. The personification andÂ  hyperbole types dominate every poem of Robert Burns. Second, the meaning of figurative language used by Robert Burns in his poems in general describe about love feelings, natural atmosphere, and social status in his era. Â Â Keywords: Poems, Figurative language, Robert Burns.